2016
DOI: 10.1177/1012690215581605
|View full text |Cite
|
Sign up to set email alerts
|

‘Wushu belongs to the world’. But the gold goes to China…: The international development of the Chinese martial arts

Abstract: Since the mid-1980s, China has been promoting wushu (also known as kung fu) as an international competitive sport towards Olympic recognition. But despite the efforts of the International Wushu Federation, to date, wushu has not entered the Olympics. Data were collected of countries' medal winning performances at the World Wushu Championships since 1991. The findings of this study clearly showed China's unchanged dominant position, thereby making it questionable if wushu has really turned into an international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 12 publications
2
34
0
Order By: Relevance
“…Wushu is characterised by its close connection with Chinese culture as it is blended with ancient Chinese philosophical ideas and religious elements (including, for example, yin and yang, Buddhism and Taoism) (Lorge, 2012). Theeboom et al (2017b) indicated that over the years, wushu practice has undergone a number of distinctive changes in content, appearance, function, as well as in training intention. As a result, two main types can be distinguished: ‘traditional’ wushu (or folk wushu); and ‘modern’ wushu (or competitive wushu).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wushu is characterised by its close connection with Chinese culture as it is blended with ancient Chinese philosophical ideas and religious elements (including, for example, yin and yang, Buddhism and Taoism) (Lorge, 2012). Theeboom et al (2017b) indicated that over the years, wushu practice has undergone a number of distinctive changes in content, appearance, function, as well as in training intention. As a result, two main types can be distinguished: ‘traditional’ wushu (or folk wushu); and ‘modern’ wushu (or competitive wushu).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the second perspective, action movies, Theeboom et al (2017b) indicated that the distribution of Kung fu movies from the late 1960s also facilitated wushu’s international dissemination. Through his movies in the early 1970s, martial artist and movie action star Bruce Lee, has been considered by many to have played an important role in the introduction of Chinese wushu to Western audiences (Judkins, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was developed in 1960 for competitive purposes with specific rules and equipment (Vasconcelos & Del Vecchio, 2017). The matches last until 3 rounds of 2 min each with 1-min intervals in between and occur in a squared elevated platform (leitai) 80 cm high and 800 cm long and wide, coated with shock-absorbing materials (Theeboom, Zhu, & Vertonghen, 2017). Athletes use motor actions such as punches, kicks, and throws, demanding speed, precision, and power, which are considered unimpeachable physical capacities for competitive success in this modality (Deng, 2017;Theeboom et al, 2017;Vasconcelos & Del Vecchio, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The matches last until 3 rounds of 2 min each with 1-min intervals in between and occur in a squared elevated platform (leitai) 80 cm high and 800 cm long and wide, coated with shock-absorbing materials (Theeboom, Zhu, & Vertonghen, 2017). Athletes use motor actions such as punches, kicks, and throws, demanding speed, precision, and power, which are considered unimpeachable physical capacities for competitive success in this modality (Deng, 2017;Theeboom et al, 2017;Vasconcelos & Del Vecchio, 2017). Regarding technical aspects and specific motor characteristics, wushu sanda is classified as a mixed-orientation combat sport, with striking (punches and kicks) and grappling (throwing) actions (Del Vecchio, Silva, & Farias, 2015;Silva, Del Vecchio, Picanço, Takito, & Franchini, 2011).…”
Section: Introductionmentioning
confidence: 99%